The levels of NF-κB p50 and NF-κB p65 play a role in thyroid carcinoma malignancy in vivo - Le, Fei (J Int Med Res, 2018)
BACKGROUND: To investigate the relationship between the levels of nuclear factor (NF)-κB p50 and NF-κB p65 and tumour characteristics in patients with thyroid carcinoma. METHODS: This prospective study enrolled consecutive patients with thyroid carcinoma. Tumour samples were collected and the levels of NF-κB p50 and NF-κB p65 protein and mRNA were measured using immunohistochemistry and quantitative real-time reverse transcription–polymerase chain reaction (qRT–PCR). RESULTS: A total of 73 patients with thyroid carcinoma were included in the study (20 males; 53 females; mean ± SD age, 44.8 ± 12.7 years, range, 18–76 years). There were no significant differences in sex, age and pathological type between the NF-κB p50 positive group and the NF-κB p50 negative group, but tumour diameter and lymph node metastasis were significantly higher in the NF-κB p50 positive group compared with the NF-κB p50 negative group. Similar findings were observed for NF-κB p65. The levels of NF-κB p50 were positively correlated with NF-κB p65 in samples of thyroid carcinoma (r(s) = 0.653). CONCLUSION: The levels of NF-κB p50 and NF-κB p65 in samples of thyroid carcinoma were positively associated with tumour diameter and the presence of lymph node metastasis.